Calvyn oor twyfel - P. C. Potgieter (Acta Theologica)
Little regarding doubt and uncertainty in matters of faith is found in publications on Calvin’s life and theology. This paper pursues his views on this topic in his Institutes, commentaries, tracts, and letters. This is done by referring to the exact words in die original Latin and French. He regards doubt as a serious consequence of sinful human nature, causing anxiety and conflict in the faithful. Although it is part and parcel of Christian life, he condemns it as opposed to the will of God. He does, however, also express his compassion with those suffering under this duress. God expects the faithful to actively resist temptations of doubt and uncertainty. The key to victory is being in Christ, whose Father is also our Father, in the power of the Holy Spirit.